PENGENDALIAN RUANG TERBUKA HIJAU (STUDI TENTANG PEMANFAATAN TAMAN KOTA DI KECAMATAN SUMUR BANDUNG KOTA BANDUNG) - Rafih Sri Wulandari (FISIP Universitas Langlangbuana, 2020)
This research was motivated by the lack of fulfillment of the standard green park open space in Bandung City, Sumur District, Bandung, Bandung City. In the analysis of aspects of control, the researcher formulated the problem as follows How to control urban green open space (RTH) in the Sumur Bandung Subdistrict, Supporting and inhibiting factors in meeting the standards of urban green open space (RTH) in the ​​Sumur Bandung District, Any effort taken to meet the standard of urban green open space (RTH) in the ​​Sumur Bandung District. Based on the model of the above framework, the researcher formulates the following propositions, Control of green open space (RTH) City Parks in the Sumur Bandung District Area by the Bandung City Parks Service meets the standards through an approach to control methods consisting of direct control, indirect control and control based on exceptions, The inhibiting factors in controlling urban green open space in the Sumur Bandung District Area by the Bandung City Parks Agency by means of control, Optimal efforts to meet City Park standards that are feasible can be carried out by means of control. The research method used in this study is a descriptive research method with a qualitative approach. Data was obtained through participant observation, in-depth interviews, and documentation. The results of this study indicate that the control of urban park green open space in the Bandung District of Bandung’s Sumur District based on Regional Regulation No. 18 concerning the Regional Spatial Plan (RTRW) of Bandung City does not meet the standards of spatial use in accordance with the Regional Spatial Plan (RTRW), there are several inhibiting factors. To overcome utilization barriers, various efforts have been made in the participation of the community or park users, among others: Appeal for environmental preservation, especially city parks, to create an environmental community. But still there is a lack of participation or lack of awareness from the community and park users. Increase public understanding of green open spaces, especially city parks. The existence of periodic supervision and implementation of green open space, the community should be involved in at least the influential people such as community leaders, in order to foster a sense of responsibility.